2013
DOI: 10.2174/1566524011313040008
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin, Somatostatin Analogs and Somatostatin Receptor Dynamics in the Biology of Cancer Progression

Abstract: The pharmacological effects (i.e., inhibition of endocrine secretion and cell proliferation) mediated by the hormone somatostatin (SRIF) are derived from its universal high-affinity binding to five different G proteincoupled receptors (GPCRs), named sst1-5. However, SRIF has a half-life of less than 3 min, whereas the available mono- and bi-specific SRIF preferential analogs show prolonged half-life and increased potency. These compounds may control tumor development, cell proliferation and metastatization by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 171 publications
0
22
0
1
Order By: Relevance
“…SST3 is a pleiotropic neuropeptide widely distributed throughout the organism, which regulates a plethora of physiological functions, including inhibition of basal and stimulated secretion from endocrine and exocrine cells, inhibition of gastrointestinal motility, modulation of neurotransmission, metabolism and immune function, as well as inhibition of cell proliferation and differentiation13456. In contrast, CORT7 is mainly produced in the cerebral cortex and was originally identified for its role in the modulation of sleep cycles, neuronal activity and immune system7891011.…”
mentioning
confidence: 99%
“…SST3 is a pleiotropic neuropeptide widely distributed throughout the organism, which regulates a plethora of physiological functions, including inhibition of basal and stimulated secretion from endocrine and exocrine cells, inhibition of gastrointestinal motility, modulation of neurotransmission, metabolism and immune function, as well as inhibition of cell proliferation and differentiation13456. In contrast, CORT7 is mainly produced in the cerebral cortex and was originally identified for its role in the modulation of sleep cycles, neuronal activity and immune system7891011.…”
mentioning
confidence: 99%
“…Somatostatin receptors (SSTR) have been recognised as dynamic regulators of tumour development, cell proliferation and apoptosis (Ruscica et al , 2012). Somatostatin secretion is known to negatively influence VEGF production (Mentlein et al , 2001), and in vitro work has shown that the administration of the somatostatin analogue octreotide can antagonise Hif-1 α transcriptional activity in NET cells (Villaume et al , 2010).…”
mentioning
confidence: 99%
“…Somatostatin system SRIF is a cyclic polypeptidic hormone largely expressed in hypothalamus which displays inhibitory functions on hormone secretion (5-18) and cell proliferation (14,19,20). SRIF acts on target cells through its binding with five specific receptor subtypes codenamed SS1R-SS5R (21,22,44,45).…”
Section: Neuroendocrine Differentiation Of Prostate Cancermentioning
confidence: 99%
“…Improved understanding of PCa biology has led to new promising treatment strategies, in particular peptide-based agonists and antagonists, including somatostatin (SRIF) analogs (SSAs), alone or in combination with other treatments (2)(3)(4). SRIF is a cyclic polypeptidic hormone largely expressed in hypothalamus which displays inhibitory functions on hormone secretion (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) and cell proliferation (14,19,20). SRIF acts through the binding with five specific membrane receptors (SSRs) codenamed SS1R-5 (21).…”
Section: Introductionmentioning
confidence: 99%